2018
DOI: 10.11648/j.jdmp.20180401.11
|View full text |Cite
|
Sign up to set email alerts
|

Ethnobotanical Survey and Biological Activities of Two Lactogenic Plants in the Cascades Region of Burkina Faso

Abstract: An ethnobotanical survey for a better knowledge of lactogenic plants has been conducted in Cascades region of Burkina Faso. Biological activities of the two most used plants were evaluated. The survey concerned 25 species classified into 22 genera and 19 families. The most represented families were Moraceae, Apocynaceae, Fabaceae-Caesalpinioideae and Malvaceae. The most used species were Euphorbia hirta, Calotropis procera and Ficus sycomorus with respectively 16.98%, 13.21% and 13.21% followed by Ficus platyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…The naming may have its origin in the production and secretion of a white milk sap that is strikingly similar to regular milk, or due to its effect on breast milk production. The use of Euphorbia hirta as a galactagogue was recorded once in our study but also known from previous studies [11,24,26] and mentioned as a milk "cleaning" plant as well. The latter application could be related to its antidiarrhoeic activity [76] and antibacterial effects against some gram-positive bacteria, causing enteric infections [61].…”
Section: Ethnological Perspectivesupporting
confidence: 80%
See 1 more Smart Citation
“…The naming may have its origin in the production and secretion of a white milk sap that is strikingly similar to regular milk, or due to its effect on breast milk production. The use of Euphorbia hirta as a galactagogue was recorded once in our study but also known from previous studies [11,24,26] and mentioned as a milk "cleaning" plant as well. The latter application could be related to its antidiarrhoeic activity [76] and antibacterial effects against some gram-positive bacteria, causing enteric infections [61].…”
Section: Ethnological Perspectivesupporting
confidence: 80%
“…According to Neuwinger [ 10 ], these galactagogues are agents that promote the secretion of milk or increase milk flow. The use of galactagogue herbs by women around the world have been recorded in previous studies [ 11 15 ]. A study conducted in the neighbouring country also showed the use of five galactagogues by the rural population [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Aspilia africana is one of the most valuable medicinal plants in the wild and is widely used in communities where it occurs (Okoli et al, 2007;Eweka and Eweka, 2008;Okello and Kang, 2019;Niyonizigiye et al, 2020). In Uganda, A. africana is 1 of the top 17 most effective herbal plants used for the treatment of malaria (Okello and Kang, 2019) and in Cameroon, it is the most commonly used plant for treating wounds (Simbo, 2010). Aspilia africana is indigenous to East Africa, although it occurs in forest zones in all regions of tropical Africa and the savanna in countries such as Tanzania, Uganda, Congo, Ghana, Liberia, Sudan, Central African Republic, Mali, Ethiopia, Cameroon, Burkina Faso, Nigeria, Senegal, and Niger (Komakech et al, 2019;Okello et al, 2020).…”
Section: Introductionmentioning
confidence: 99%